Pengaruh Kualitas Pelayanan Aplikasi PLN Mobile, Terhadap Loyalitas Dengan Kepuasan Pelanggan Sebagai Interverning (Studi pada Pelanggan PT PLN Persero UP3 Malang) - Guterres, Novicasari Nur Pratiwi; Arifin, Rois; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research to analyze and describe the influence of PLN Mobile Application Service Quality on Loyalty with Customer Satisfaction as Interverning (Study on PT PLN Persero UP3 Malang Customers. The population in this study is PLN mobile UP3 Malang users with a total of 35,574 users. Then from the total A sample of 98 people was taken using the Slovin formula. The variables used in this research were the dependent variable customer loyalty, the independent variable service quality, and the intervening variable customer satisfaction. The data analysis technique in this research used path analysis with the help of SPSS 26 software research shows that 1). PLN Mobile Application Service Quality has a positive and significant effect on Customer Satisfaction of PT PLN Persero UP3 Malang.2). PLN Mobile Application Service Quality has a positive and significant effect on customer loyalty of PT PLN Persero UP3 Malang. 3). Customer Satisfaction has a positive and significant effect on customer loyalty of PT PLN Persero UP3 Malang. 4). The service quality of the PLN Mobile Application has a positive and significant effect on customer loyalty through customer satisfaction at PT PLN Persero UP3 Malang. Keywords: Service Quality, Customer Loyalty, Customer Satisfaction